ANALYSIS OF MATHEMATICAL CREATIVE THINKING ABILITY IN TERMS OF SELF-REGULATED LEARNING IN THE CREATIVE PROBLEM-SOLVING LEARNING MODEL - Agustina, Vena; Masrukan, Masrukan; Walid, Walid (De Fermat : Jurnal Pendidikan Matematika, 2022)
This research aims to test the effectiveness of Creative Problem Solving (CPS) learning and to describe students' mathematical creative thinking skills in terms of Self-Regulated Learning (SRL). The method used is a mixed method research with a sequential explanatory design. In this research, 6 research subjects were taken based on the level of SRL in class VIII A students of SMP Negeri 1 Tayu, Pati Regency for the academic year 2022/2023. The results showed that (1) the CPS learning model was effective on students' mathematical creative thinking abilities, and (2) research subjects with high SRL categories were able to meet all indicators of mathematical creative thinking ability, namely fluency, flexibility, originality, and elaboration; research subjects with moderate SRL category only met three indicators of mathematical creative thinking ability, namely fluency, originality, and elaboration; research subjects with low SRL category can’t meet all indicators of mathematical creative thinking ability. Recommendations to students with low levels of SRL can’t meet all indicators of mathematical creative thinking ability by giving assignments independently and doing peer teaching.